Formulating an Accounting Education Objectives Concept: Based on The Sluku-Sluku Bathok Song - Binti Shofiatul Jannah; Alvien Gunawan; Titik Agus Setiyaningsih; Ni Made Intan Priliandani (The Indonesian Accounting Review, 2025)
This study is motivated by indicating that accounting is vulnerable to using only rational reason. The dominance of rational reason in accounting education is inseparable from the agency theory taught by accounting educators. Therefore, this study aims to build a concept of accounting education objectives based on the “sluku-sluku bathok” song. This study uses Fairclough's (1992) discourse analysis, which includes text analysis, discursive practices, and social practices. The text analysis stage identifies the lyrics of the "sluku-sluku bathok" song. The discursive practice stage is to interpret the "sluku-sluku bathok" song. The social practice stage is to explore how this song reflects the values ​​of Javanese society. As a result, the objectives of accounting education are complete with values. First, accounting education is a process of seeking actual knowledge. Second, accounting education balances dhikr and thought. Third, accounting education is about gaining pleasure in the world and the hereafter. The "pleasure” in question is the true pleasure of meeting God in the hereafter. The results of this study open up a new path in accounting education, with the hope of producing accounting professionals who not only have technical competence but are also strong in character building and can balance worldly and spiritual aspects.